Identifikasi komponen bioaktif dan aktivitas antibakeri rumput laut cokelat (Sargassum plagyophyllum) terhadap bakteri Staphylococcus aureus dan Escherichia coli - Noor Ira Sari; Indah Azisari; Andarini Diharmi (AGROINTEK, 2024)
Sargassum plagyophyllum is a type of brown seaweed containing bioactive components including alkaloids, flavonoids, steroids/terpenoids, saponins and phenolics that have potential as antibacterial. This study aims to determine the bioactive components of the S. plagyophyllum extract fraction qualitatively and the antibacterial activity of the S. plagyophyllum fraction by agar diffusion method with wells. The method used in this research is an experiment by extracting and fractionating S. plagyophyllum. Parameter analysis consisted of analysis of bioactive components (alkaloids, flavonoids, steroids/terpenoids, saponins, phenolics) qualitatively and determining antibacterial activity in the S. plagyophyllum fraction against Staphylococcus aureus and Escherichia coli. The results showed that the bioactive components in the methanol extract of S. plagyophyllum contained flavonoids, steroids/terpenoids, saponins and phenolic compounds. The bioactive components in the ethyl acetate fraction contained alkaloids, flavonoids, steroids/terpenoids, saponins and phenolics. The n-hexane and butanol fractions contained steroids/terpenoids, and saponins. The extract fraction of S. plagyophyllum could inhibit the growth of antibacterial activity against S. aureus and E. coli bacteria. The ethyl acetate fraction was the best fraction inhibiting bacterial activity with the highest zone of inhibition compared to other fractions (n-Hexane and buthanol), namely 12.95 ± 0.64 mm for S. aureus bacteria and 10 ± 0.14 mm for E. coli bacteria.